PEMBERDAYAAN KADER KESEHATAN REPRODUKSI MELALUI PEMERIKSAAN MIKROPENIS DAN HIPOSPADIA SISWA SDN MODEL BANYUWANGI KABUPATEN BANYUWANGI - I'tishom, Reny; Agustinus, Agustinus; Rezkiawan, Ditto; Indarto Susilo, Rahadian; Syahrizal Pasaribu, Wanly; Lionardi, Samuel; Putri Handini, Lika; Melka Parmanto, Cristian; Susanto, Natasha; Maulana Ishom Putra, Wildan; Setiono, Budi (Jurnal Abdi Insani, 2024)
Cases of micropenis and hypospadias are like the tip of the iceberg, as many parents are yet to identify and be aware enough to have their child's abnormalities checked by a doctor. Micropenis and hypospadias abnormalities can be well managed if detected before puberty, but parents' long-term ignorance can lead to infertility, malignancy, and urinary dysfunction in their children. Education aims to increase parents' knowledge and awareness to detect genital abnormalities in boys, so they can be addressed as early as possible. So far, there is no data on micropenis cases, hypospadias cases, or the average penis length in elementary school students, thus genital examinations in elementary school students are crucial for screening and obtaining accurate data. Activity Method: Parents and teachers will be asked to take a pre-test, then attend education sessions on micropenis and hypospadias, followed by discussions and Q&A sessions. A post-test will be conducted to test the participants' understanding of the education. Participants who agree for their sons to undergo physical and genital examinations will be examined in the school health unit (UKS). Results: A total of 39 male students participated with an average age of 10.77 ± 1.05 years. Cases of phimosis were found in 3 individuals, buried penis in 5 individuals, high-placed testes in 2 individuals, and varicocele in 1 individual. No cases of micropenis or hypospadias were found. The average penis length was 6.76 ± 1.78 cm, the right testis volume was 4.10 ± 2.10 ml, and the left testis volume was 4.13 ± 2.19 ml. Conclusion: Although no cases of micropenis and hypospadias were found in students, other genital abnormalities such as phimosis, buried penis, high-placed testes, and varicocele were detected.